Characterizing the relationship between Sortase A-dependent substrates and the consequences of Srta deletion in Enterococcus faecalis - Afonina, Irina (2017)
Enterococcus faecalis is a gastrointestinal commensal bacterium that has emerged as an important opportunistic pathogen that is a serious public health threat due to its prevalent antibiotic resistance. A variety of virulence factors contributes to the pathogenesis of Enterococci, including Sortase A (SrtA) and several SrtA substrates including endocarditis and biofilm associated pili (Ebp), adhesin of collagen from Enterococci (Ace), and aggregation substance (AS). Understanding the expression relationship between SrtA and its substrates, as well as the expression relationship and any cross-regulation between SrtA substrates, is crucial to effectively target bacterial adhesion for the reduction of virulence in the future. In this thesis, we showed that SrtA substrate expression does not depend on the presence of SrtA, and that Ebp accumulate in the plasma membrane in ∆srtA resulting in increased piliation. We showed that DnaK is important for Ebp biogenesis and that dnaK transcription is higher in ∆srtA, suggesting that DnaK may have a role in processing additional SrtA substrates. We explored the possibility that accumulation of unprocessed substrates in ∆srtA would result in increased vesiculation, which is associated with membrane stress in other organisms, but instead detected a similar number of membrane vesicles (MV) between WT and ∆srtA. However, as a result of increased membrane-associated Ebp, MV from ∆srtA were enriched in Ebp. Analysis of MV protein composition and high-resolution imaging of MV led us to hypothesize several mechanisms for MV formation via explosive cell lysis, through cell-wall modifying enzymes or from microdomains. Lastly, we addressed the expression relationships between Ebp, AS, and Ace. When Ebp and AS are expressed on the same cells, Ebp prevent AS-mediated clumping and decreases the frequency of horizontal gene transfer between AS-expressing cells. We also observed temperature-dependent differential expression of Ebp and Ace, suggesting that the two adhesins might be inversely regulated by environmental cues. Taken together these findings enhance our understanding of SrtA, Ebp, and cell-envelope biogenesis in E. faecalis, and provide new insight into the expression relationship between multiple enterococcal adhesins.